Brain control of blood glucose levels: implications for the pathogenesis of type 2 diabetes - Alonge, Kimberly M. (Diabetologia, 2020)
Despite a rapidly growing literature, the role played by the brain in both normal glucose homeostasis and in type 2 diabetes pathogenesis remains poorly understood. In this review, we introduce a framework for understanding the brain’s essential role in these processes based on evidence that the brain, like the pancreas, is equipped to sense and respond to changes in the circulating glucose level. Further, we review evidence that glucose sensing by the brain plays a fundamental role in establishing the defended level of blood glucose, and that defects in this control system contribute to type 2 diabetes pathogenesis. We also consider the possibility that the close association between obesity and type 2 diabetes arises from a shared defect in the highly integrated neurocircuitry governing energy homeostasis and glucose homeostasis. Thus, whereas obesity is characterised by an increase in the defended level of the body’s fuel stores (e.g. adipose mass), type 2 diabetes is characterised by an increase in the defended level of the body’s available fuel (e.g. circulating glucose), with the underlying pathogenesis in each case involving impaired sensing of (or responsiveness to) relevant humoral negative feedback signals. This perspective is strengthened by growing preclinical evidence that in type 2 diabetes the defended level of blood glucose can be restored to normal by therapies that restore the brain’s ability to properly sense the circulating glucose level.